Kodifikasi Hadis Sebagai Fondasi Hukum Islam Pada Era Umar Bin Abdul Aziz Daulah Umayyah di Damaskus 717-720 M - Nur Rachmah Catur Setyaningsih; Dzulkifli Hadi Imawan (Batuthah: Jurnal Sejarah Padaban Islam, 2025)
The codification of hadith in early Islam has received limited attention as a foundational stage in developing a systematic and institutionalized Islamic legal system. Most studies focus on the Abbasid period, whereas the Umayyad Caliphate played a crucial role in the transition from oral traditions to written law. This article analyzes the role of hadith codification as a foundation of early Islamic law, particularly through the contributions of key figures such as Umar ibn Abd al-Aziz and Imam al-Zuhri. This study employs a qualitative-historical approach combined with library research, using content analysis to identify main themes, codification patterns, and political-legal strategies. The historical approach examines the socio-political and legal context of Umar ibn Abd al-Aziz’s reign, while library research draws on primary sources, such as classical hadith collections and historical chronicles, alongside secondary academic literature. Findings indicate that hadith codification under Umar ibn Abd al-Aziz marked a pivotal transformation of Islamic law from oral and localized forms to a written, standardized, and transregional structure. Beyond preventing forged hadith, codification functioned as a political strategy to unify legal authority and laid the groundwork for legal methodologies that shaped classical Islamic legal traditions.